The shadow-boxing woman - Parei, Inka (German list., 2011)
"... a decaying apartment building in post-Wall Berlin is home to Hell, a young woman with a passion for martial arts. When Hell's neighbour disappears she sets out across the city in search of her. In the course of her quest, she falls in love with a bank robber, confronts her own dark memories, and ends up saving more than just her missing neighbour..."--Book jacket.